Sony / Abdullah Aiman Aziz - Aziz, Abdullah Aiman (2022)
This case study is about identifying the issue regarding the electronic device chosen. The company that have been chosen is Sony, one of the most famous electronic device producer in Malaysia. Sony have supply a lot of well-known device such as camera and video recorder. The device that I have chosen produce from the Sony for my case study is PlayStation4 Dual Shock 4 wireless Controller. For this case study, some research background have been done in order to collect some information regarding their background, product and service. The SWOT analysis also have been done in order to analyses the strength, weakness, opportunity and thread for the PS4 Dual Shock controller. Three problems or issues have been identify for this electronic device and the main problem is the poor battery lifespan’s product. From the main problem identified, three solution have been identify and the best solution to solve this main problem is to increase the battery capacity.